Children's Comprehension of War - Miljević-Riđički, Renata; Lugomer-Armano, Goranka (1994)
The purpose of this paper is to show how pre-school children, both from Zagreb and refugees, experienced and comprehended the war during 1992. The study included 98 children from Zagreb kindergartens (pre-school nurseries). The children were asked five questions about the war in Croatia. Each was interviewed individually. A content analysis of the answers revealed that the children, in defining the warring parties and the causes of the war, besides using much information obtained through the media, based their concepts of the war on personal experience. The worst war-related experience for Zagreb children was the air-raid alarms, while the displaced or refugee children felt worst when there were bombardments, destruction and shooting - mostly personally experienced events. Generally, the children's answers suggest more mature comprehension of war than usually expected and found at the pre-school age.
ENG